O efeito estético e o afetar o outro em A Bela e a Fera na literatura e no cinema: da leitura e da figura feminina - Borges, Pleybsonvytsions Ferreira de Souza (2023)
The aim of this study is to analyze the literary reception of "Beauty and the Beast", written by Madame Villeneuve. The approach adopted is hermeneutics, based on the aesthetics of reception, which places the reader as the guarantor of the historicity of the literary work. Both the aesthetic effect and the reader's reception are central elements in the critical approach of this dissertation. In the first part, the concept of "art" is explored from a hermeneutic perspective that allows a multiplicity of meanings and analyzes the impact that the work causes on the reader, as well as its understanding and interpretation during the aesthetic reception. In this context, the relationship between the work and the subject who appreciates it aesthetically stands out, with emphasis on the textual cooperation mechanism and the reader's skills in (re)reading the work's corpus, whether in literature or cinema, with the aim of starting point the representation of the female figure in modernity. Furthermore, the concept of "affect" and "perceptual" proposed by Deleuze & Guattari will be approached, enriching the critical analysis of the literary reception in question